Expanding the chemistry of borates with functional [BO2]− anions - Chunmei Huang; Miriding Mutailipu; Fangfang Zhang; Kent J. Griffith; Cong Hu; Zhihua Yang; John M. Griffin; Kenneth R. Poeppelmeier; Shilie Pan (Nature Communications, 2021)
Borates offer extended structural diversity and promise in diverse applications. Here the authors report a borate with linear BO2 units as well as NMR spectroscopy characterization that provides a quantitative basis for identification of BO2 units in polycrystalline and non-crystalline samples.